2014
DOI: 10.1111/bij.12362
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic evolution of an Atlantic Forest passerine (Xiphorhynchus fuscus): biogeographic and systematic implications

Abstract: We studied the phenotypic variation of the Atlantic Forest passerine Xiphorhynchus fuscus (Aves: Dendrocolaptidae) with the broad aim of addressing whether the history and type of forest affected the evolution of endemic taxa. We also tested whether the different subspecies and genetic lineages of X. fuscus could be considered full species. We collected plumage and body size measurements and, in combination with genetic data, used multivariate tests to evaluate the working hypotheses. Our results, combined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
(99 reference statements)
1
10
0
2
Order By: Relevance
“…The importance of the Doce River and Todos os Santos Bay disjunctions are corroborated by many studies using different methods and taxa ( Müller 1973 ; Prance 1982 ; Amorim and Pires 1996 ; Silva et al 2004 ; Pellegrino et al 2005 ; Sigrist and Carvalho 2009 ; Brunes et al 2010 ; Thomé et al 2010 ; Silva et al . 2012 ; Cabanne et al 2014 ); the latter has also been associated with the São Francisco River ( Carnaval and Moritz 2008 ). DaSilva et al (2015) provided detailed geographical and historical information on the barriers between areas of endemism for harvestmen and also showed that the Todos os Santos Bay should receive more attention from biogeographers, because it is more closely associated with the range limits of endemic species (see also Amorim and Pires [1996 ] and Silva et al [2012 ]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of the Doce River and Todos os Santos Bay disjunctions are corroborated by many studies using different methods and taxa ( Müller 1973 ; Prance 1982 ; Amorim and Pires 1996 ; Silva et al 2004 ; Pellegrino et al 2005 ; Sigrist and Carvalho 2009 ; Brunes et al 2010 ; Thomé et al 2010 ; Silva et al . 2012 ; Cabanne et al 2014 ); the latter has also been associated with the São Francisco River ( Carnaval and Moritz 2008 ). DaSilva et al (2015) provided detailed geographical and historical information on the barriers between areas of endemism for harvestmen and also showed that the Todos os Santos Bay should receive more attention from biogeographers, because it is more closely associated with the range limits of endemic species (see also Amorim and Pires [1996 ] and Silva et al [2012 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Since the Neogene period, these characteristics allowed for a greater reduction of the forests in these regions because of climatic fluctuations that would cause feedback to facilitate their instability. This model of diversification of reiterative barriers with spatial congruence at multiple times would respond to claims of individual taxa history when it is shown that different taxa diverge at different times in the same barrier ( Brunes et al 2010 ; Thomé et al 2010 ; Cabanne et al 2014 ). This represents an argument against pseudo-congruence ( Donoghue and Moore 2003 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without knowledge of the exact genomic basis and heritability of these traits, it is difficult to precisely determine which forces have shaped phenotypic variation (Mitchell_Olds et_al.,_2007). However, when combined with genome_wide genetic data, phenotypic information can provide insight into which mechanisms might have played a role in driving the origins of phenotypic variation (Cabanne, Trujillo_Arias, Calder_n, D_Horta, & Miyaki,_2014; Rausher & Delph,_2015). For example, if geographical patterns of phenotypic variation coincide closely with historical barriers to dispersal (IBH) or change clinally with geographical distance (IBD), phenotypic differences among populations might have evolved primarily as a byproduct of genetic drift, potentially reinforced by natural selection across the barrier or along the cline (Lande,_1980).…”
Section: Introductionmentioning
confidence: 99%
“…Without knowledge of the exact genomic basis and heritability of these traits, it is difficult to precisely determine which forces have shaped phenotypic variation (Mitchell-Olds et al, 2007). However, when combined with genome-wide genetic data, phenotypic information can provide insight into which mechanisms might have played a role in driving the origins of phenotypic variation (Cabanne, Trujillo-Arias, Calderón, D'Horta, & Miyaki, 2014;Rausher & Delph, 2015).…”
mentioning
confidence: 99%